(9/3)+(4+5)(7*8)(8/9)+(6-7)
Answers
Answered by
0
Hey!!!
________________________________
![( \frac{9}{3} ) + (4 + 5)(7 \times 8)( \frac{8}{9}) + (6 - 7) \\ = 3 + (9 \times 56 \times \frac{8}{9} ) + ( - 1) \\ = 3 + 448 - 1 \\=451-1 \\ = 450 ( \frac{9}{3} ) + (4 + 5)(7 \times 8)( \frac{8}{9}) + (6 - 7) \\ = 3 + (9 \times 56 \times \frac{8}{9} ) + ( - 1) \\ = 3 + 448 - 1 \\=451-1 \\ = 450](https://tex.z-dn.net/?f=%28+%5Cfrac%7B9%7D%7B3%7D+%29+%2B+%284+%2B+5%29%287+%5Ctimes+8%29%28+%5Cfrac%7B8%7D%7B9%7D%29+%2B+%286+-+7%29+%5C%5C+%3D+3+%2B+%289+%5Ctimes+56+%5Ctimes+%5Cfrac%7B8%7D%7B9%7D+%29+%2B+%28+-+1%29+%5C%5C+%3D+3+%2B+448+-+1+%5C%5C%3D451-1+%5C%5C+%3D+450)
________________________________
Hope it helps!!! :)
________________________________
________________________________
Hope it helps!!! :)
Answered by
0
Here ,
=9/3+9*56*8/9+(6-7)
=9/3+56*8+(-1)
=3+448-1
=451-1
=450
Thanks
=9/3+9*56*8/9+(6-7)
=9/3+56*8+(-1)
=3+448-1
=451-1
=450
Thanks
Similar questions